Dexamethasone, dexamethasone + remdesivir in treating moderate to severe COVID-19: retrospective observational cohort study - Nithish Sattoju; Santosh Gattu; Sai Sashank Merugu; Vydhika Anneboina; Sai Ram Ganapaka (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to demonstrate the purpose of adding antiviral (remdesivir) to the existing steroidal (dexamethasone) therapy in treating coronavirus disease 2019 (COVID-19).